Implementation of dam safety management program in malaysia: From theory to practice - Lariyah M.S.; Hidayah B.; Thiruchelvam S.; Rahsidi S.M.; Azwin Zailti A.R.; Zuraidah A. (Trans Tech Publications Ltd, 2023)
Dam plays vital roles to mankind since the beginning of civilization. It serves the purpose for water supply, irrigation, hydropower and flood control. Despite the benefits of dam served over a decade, dams also poses high risk especially to the people downstream, as it may fail due to several failure modes, such as flood loading, earthquake and piping failure. History proved that dam failure has caused catastrophic impact to the people and environment. The dam owner is responsible to ensure that their dam is safe to the public and environment. In Malaysia, the key utility company, Tenaga Nasional Berhad has proactively played its role as the owner of the largest hydropower scheme by spearheading the effort of developing its own dam safety program. This paper revolves around the journey of TNB in developing an Emergency Response Plan (ERP) as part of their dam safety program. © (2014) Trans Tech Publications, Switzerland.